Communities, archives and new collaborative practices - Popple, Simon; Prescott, Andrew; Mutibwa, Daniel H. (Connected communities (Bristol, England), 2020)
Using a wide range of case studies, this edited collection shows how community engagement and co-creation is challenging and extending the notion of the archive